Assessment of oral hygiene practice among school going children in Ambattur, Chennai District – A cross sectional study - Nagappan Nagappan; S. Shanmugavelu (SRM Journal of Research in Dental Sciences)
Background: Oral health is vital to general well-being, especially during childhood and adolescence. Globally, oral diseases such as dental caries and periodontal issues affect a large portion of children due to poor hygiene practices, high sugar intake, and limited access to dental care. In India, these concerns persist, particularly among school-aged children in underserved communities. Aim: This study aimed to assess oral hygiene practices, awareness, and related behaviors among school-going children in Ambattur, Chennai District. Materials and Methods: A cross-sectional study was conducted in November 2019 among 500 students aged 10–17 years at the Government Girls Higher Secondary School, Ambattur. Data were gathered using the World Health Organization Oral Health Assessment Form for Children (2013), covering hygiene habits, dental visits, diet, and hygiene aids. Clinical evaluations were conducted by a calibrated examiner, and the data were analyzed using SPSS version 21.0. Results: Of the participants, 65.6% were aged 10–12 years, 24% were 13–14 years, and 8.6% were 16–17 years. Only 26.35% had ever visited a dentist, while just 10.29% used fluoridated toothpaste. Frequent consumption of sugary foods and drinks was reported by 84.87%. Many participants expressed dissatisfaction with their oral health. Conclusion: Oral hygiene practices in the studied population were found to be inadequate, with low awareness and suboptimal preventive behaviors. There is a critical need for school-based oral health education programs to improve awareness, promote good practices, and reduce the burden of oral diseases.